2017
DOI: 10.1158/1078-0432.ccr-17-0232
|View full text |Cite
|
Sign up to set email alerts
|

Circulating DNA Demonstrates Convergent Evolution and Common Resistance Mechanisms during Treatment of Colorectal Cancer

Abstract: Purpose Liquid biopsies allow the tracking of clonal dynamics and detection of mutations during treatment. Experimental design We evaluated under blinded conditions the ability of cell free DNA (cfDNA) to detect RAS/BRAF mutations in the plasma of 42 metastatic colorectal cancer patients treated on a phase Ib/II trial of FOLFOX and dasatinib, with or without cetuximab. Results Prior to treatment, sequencing of archival tissue detected mutations in 25/42 patients (60%), while the cfDNA assay detected mutati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 60 publications
(69 reference statements)
5
76
0
1
Order By: Relevance
“…cfDNA can be used to monitor acquisition of resistance, through screening for known resistance mutations , or searching for novel mechanisms of resistance . Serial sampling can be performed to identify resistant clones prior to the onset of clinical progression .…”
Section: Clinical Applications Of Cfdnamentioning
confidence: 99%
“…cfDNA can be used to monitor acquisition of resistance, through screening for known resistance mutations , or searching for novel mechanisms of resistance . Serial sampling can be performed to identify resistant clones prior to the onset of clinical progression .…”
Section: Clinical Applications Of Cfdnamentioning
confidence: 99%
“…In patients with advanced cancers, it is clear that the tumor genome continues to evolve with time and with the pressure exerted on cells by treatments that selectively favor the growth of treatment‐resistant subclones . Investigators remain concerned about clonal evolution and often will recommend rebiopsy of tumors when patients have refractory disease to ensure that the genomic analysis used to make informed decisions about clinical trials with targeted agents is reflective of the tumor's current biology . Others suggest testing at the first sign of advanced disease, as the efficacy of conventional chemotherapy is variable and strategies for salvage therapy may be required sooner rather than later.…”
Section: Challenges and Open Questions In Molecular Profilingmentioning
confidence: 99%
“…178 Investigators remain concerned about clonal evolution and often will recommend rebiopsy of tumors when patients have refractory disease to ensure that the genomic analysis used to make informed decisions about clinical trials with targeted agents is ref lective of the tumor's current biology. 179 Others suggest testing at the first sign of advanced disease, as the efficacy of conventional chemotherapy is variable and strategies for salvage therapy may be required sooner rather than later. The use of "liquid biopsies" either on circulating tumor cells or on cell-free DNA has been touted as a method of assessing the tumor genome without the need for a repeat, invasive biopsy.…”
Section: Timingmentioning
confidence: 99%
“…In fact, largescale sequencing projects of ctDNA showed that genetic alterations present in primary tumors can also be found in ctDNA (Strickler et al, 2018;Zill et al, 2018). Furthermore, serial ctDNA analysis proves to be a powerful method to longitudinally monitor therapy response and the emergence of resistant clones (Bettegowda et al, 2014;Siravegna et al, 2015;Thierry et al, 2017). Several methods have been developed to detect mutations in ctDNA, including BEAMing technologies (Diaz et al, 2012;Haselmann et al, 2018;Janku et al, 2015), panel sequencing of cancer-associated genes (Strickler et al, 2018;Zill et al, 2018), or targeted amplicon sequencing (Lebofsky et al, 2015;Tie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%